- #1
- 80
- 0
Solve:
lim x->0 (tan 3(x+h)-tan(3x))/h
i hv no clue where to start =(
lim x->0 (tan 3(x+h)-tan(3x))/h
i hv no clue where to start =(
sry, yes i mean lim h->0Did you mean lim h->0??
Yep. You don't have to use any trig. But using sec^2(A)=1+tan^2(A) would put it in the simpler form listed in books.It is actually very simple.. don't even need to any trig after simplifying tan(3x+3h) ..
should factor out things.. and they would cancel out nicely.
And, one more thing tan(x)/x = 1 .. (which is simple to prove is you know sin(x)/x =1 as x-->0)